Influences of Augmented Reality Assistance on Performance and Cognitive Loads in Different Stages of Assembly Task - Yang, Zhen; Shi, Jinlei; Jiang, Wenjun; Sui, Yuexin; Wu, Yimin; Ma, Shu; Kang, Chunyan; Li, Hongting (Frontiers in Psychology, 2019)
According to the assembly task model proposed by Stork and Schubö (2010), the assembly task is divided into commissioning and joining subtasks. Each subtask includes two sequential stages, namely, perception and response selection, and action. This division enables a convenient discussion of the influences of augmented reality assistance on operators during different stages of an assembly task. Research results can provide a basis for the further analysis of the influence mechanism of augmented reality assistance on an assembly task. This study is composed of three experiments. Experiment 1 explores the influences of augmented reality assistance on the performance of the overall assembly task and the commissioning and joining subtasks. Combining a variation of task difficulties, Experiments 2 and 3 discuss the influences of augmented reality assistance on the different stages of the commissioning and joining subtasks. We found that augmented reality assistance can shorten the time of the overall assembly task and subtasks (commissioning and joining) and reduce mistakes during these tasks. Moreover, augmented reality assistance can decrease cognitive load in the commissioning subtask, but it increases cognitive load in the simple joining task. In the perception and response selection stage of the commissioning and joining subtasks, augmented reality assistance can shorten the time for users to recognize the target part and understand the assembly relation. This advantage is extremely significant for a difficult task. In the action stage of two subtasks, augmented reality assistance can shorten the time for users to capture parts, but it prolongs the time for users to build parts.